Study of carbon nanotubes for molecular electronic applications - Zhang, Qing (2008)
Although the development of silicon based VLSI technology has progressed at a nearly exponential rate and made a huge impact on almost all aspects of human life, the technology is difficult to adapt to the high demand of next generation of electronic devices because of several serious problems, such as fundamental physical limitations, extremely high fabrication costs, etc. In contrast, molecular electronic devices can, in principle, overcome these problems, because it is possible to have single-molecule devices that are organized cheaply in parallel self-assembly. Carbon nanotubes (CNTs), depending on their diameter and helicity, behave as one-dimensional metals or semiconductors, which by virtue of their great electrical current handling capability, high thermal conductivity and high mechanical toughness, represent an ideal material for molecular/nano electronic devices. However, to fabricate practical CNT based nanoelectronic devices, people have to overcome many challenges, say efficiently patterning CNTs, understanding the unique electronic properties of CNTs and studying the interactions of CNTs with their surrounding environments, including metallic electrodes, adsorbed gas molecules, etc. In course of this project, we have paid our attention to the above mentioned issues. We have developed AC dielectrophoresis technique to assemble CNTs to desirable electrodes. With it, we have successfully developed single walled CNT based field-effect transistors (SWCNT-FETs). The performance of the SWCNT-FETs is very encouraging. Using the devices as a platform, we have attempted CNT based NH3, glucose and organophosphate sensors. In addition, several CNT related fundamental issues have been studied. With these achievements, we can say that the main objectives of the projects have been fully fulfilled. In the last phase of the project, one can note that the outcomes of the project is not only having been produced a few tens of academic research papers. The far-reaching significance of the project lies in the fact that the first-hand experience and know-how about fabrication of CNT based nanoeelctronic devices, especially, single CNT devices, have been developed. Making use of them, we are capable of developing other types of CNT devices, with which we are able to pursue further study either on the devices and their physics or low dimensional fundamental problems.